Rancangan Sistem Informasi Pengolahan Data Desa Salube Kecamatan Loloda Kepulauan Kabupaten Halmahera Utara Berbasis Website - Parti H Gisisi; Rachmat Saleh Sukur; Akil Thalib (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2022)
Abstrack - The population data processing information system is a main activity carried out by the village, where in carrying out population data processing it must be carried out quickly, precisely and accurately. However, in reality at the Salube Village Office, errors often occur in recording data and are less accurate in processing population data. In this study, a system that deviates population data is designed, this system aims to make it easier for village office staff to store population data without having to fear losing, this website can be managed by admin by logging in using the username and password that has been determined while the head login villages can only see population data that has been saved. This system was designed using the waterfaal method, Xampp where phpMyadmin as the database operator, MySQL as the database, sublime text as the code for this information system program, and the results of this information system design as data processing in Salube Village, Loloda Islands District, Halmahera Uatara Regency. Keywords : System, information, processing, Data, population